THE ROLE OF TEACHER’S GUIDANCE COUNSELING IN HANDLING TROUBLED STUDENTS - Adang Darmawan Achmad; Rasyid Sidiq; Hudzaifah Achmad Qotadah (An-Nufus, 2020)
Adolescence is a period prone to instability where they have a high curiosity about something, not except the desire to break the rules when sitting in class X Aliyah. Therefore, the guidance and counseling teacher's role is very important where the guidance and counseling teacher can act as a service room for the students in terms of fostering students with special files at Madrasah Mu'allimin. The objective of this research is to examine the role of Teacher’s Guidance Counseling in educating students of class X Aliyah Madrasah Mu'allimin Muhammadiyah Yogyakarta. This research is a type of field research where the research method is qualitative by taking the background of the Mu'allimin Muhammadiyah Yogyakarta Madrasah as the research location. Meanwhile, the results of the study indicate that the role of counseling teacher in fostering students who are involved is through various forms of approaches, for example, by socializing the rules of conduct in madrasah and dormitories, conducting case raids as a preventive effort, imposing sanctions according to the type of violation, and finally through development activities. The potential for students to actively participate in positive activities in extracurricular activities, organization, committee events, and participation in competitions.